Diasporic Subjectivities: A Study of the Second-generation Immigrant in Hiromi Goto’s Chorous of Mushrooms - Bhandari, Nagendra Bahadur (Literary Studies, 2021)
This article analyses the formation of the hybrid and multiple subjectivities of the second-generation immigrant Murasaki in Hiromi Goto’s Chorus of Mushrooms. In diaspora, Murasaki simultaneously vacillates in the cultural spaces of her homeland Japan and host land Canada. She follows cultural practices of both cultural spaces in her cultural negotiation in the diaspora. Her simultaneous vacillations in two cultural spaces render hybridity and multiplicities in her subjectivities that deconstruct bipolar notion of home and host culture. Moreover, her subjectivities involve in a constant process of formation and reformation undermining the notion of stability and consistency.Murasaki’s evolving subjectivity is analyzed through Stuart Hall’s notion of cultural identity and Homi Bhabha’s postulation of third space in this study.